Cetacean Strandings in the US Pacific Northwest 2000–2019 Reveal Potential Linkages to Oceanographic Variability - Amanda J. Warlick; Jessica L. Huggins; Dyanna M. Lambourn; Deborah A. Duffield; Dalin N. D’Alessandro; James M. Rice; John Calambokidis; M. Bradley Hanson; Joseph K. Gaydos; Steven J. Jeffries; Jennifer K. Olson; Jonathan J. Scordino; et al. (Frontiers in Marine Science, 2022)
Studying patterns in marine mammal stranding cases can provide insight into changes in population health, abundance, and distribution. Cetaceans along the United States West coast strand for a wide variety of reasons, including disease, injury, and poor nutritional status, all of which may be caused by both natural and anthropogenic factors. Examining the potential drivers of these stranding cases can reveal how populations respond to changes in their habitat, notably oceanographic variability and anthropogenic activities. In this study, we aim to synthesize recent patterns in 1,819 cetacean strandings across 26 species in the Pacific Northwest from 2000 to 2019 to compare with previous findings. Additionally, we aim to quantify the effects of localized and basin-scale oceanographic conditions on monthly stranding cases for five focal species using generalized additive models in order to explore potential relationships between strandings and changes in biophysical features that could affect foraging conditions or other important physiological cues. Our results suggest that strandings of harbor porpoises, gray whales, humpback whales, Dall’s porpoises, and striped dolphins are correlated with certain environmental variables, including sea surface temperature, chlorophyll concentration, and the Pacific Decadal Oscillation depending on the species. While it remains challenging to identify the causal mechanisms that underlie these relationships for a given species or population based on its utilization of such a complex ecosystem, improving our understanding of periods of increased strandings can enhance our knowledge of how these species interact with their environment and assist conservation and management efforts. This study enhances the utility of stranding records over time beyond simply reporting trends and has broader applicability to other geographic regions amid global climate change.